Transaminases for chiral amine synthesis - Gomm, Andrew; O'Reilly, Elaine (Elsevier, 2018)
Amine transaminases are important biocatalysts for the synthesis of chiral primary amines. Unlike many enzymes that have been employed for the synthesis of optically active amines, amine transaminases are capable of asymmetric synthesis and do not rely on costly cofactors that must be regenerated in situ. However, their application as general catalysts for the preparation of amines is hampered by a limited substrate scope, substrate and (co)product inhibition and difficulties associated with displacing challenging reaction equilibrium. There has been important progress made to overcome these challenges, including the development of enzymes with broader substrate scope and the design of methodology to effectively displace the reaction equilibrium. Amine transaminases are also being applied in an increasing range of (chemo)enzymatic cascades and immobilized for applications in flow.